Compostagem dos Resíduos da FCT/UNESP de Presidente Prudente –SP - Ortolan, Carlos Henrique Stocco [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The present work aimed to study the composting process using two methods of treatment, conventional and mechanized for the treatment of pruning/weeding waste and organic waste generated in the canteens of the FCT/UNESP. For this work, it was quantified the generation of the waste However, of the tests with pure organic compound, which had the best result was T1 - 70% RPC / 30% ROC, again indicating the feasibility of applying this condition in scales at the campus. The conventional treatment by composting was carried out on manual aerated piles: 70% residue pruning/weeding (RPC) and 30% organic waste from the canteen (ROC); 50% RPC / 50% ROC, 30% RPC / 70% ROC. The mechanized system consisted of a reactor of 190 liters – 50% RPC / 50% ROC, with air injection from a compressor for 15 minutes daily. The parameters characterized and monitored were pH, organic matter, organic carbon, ash, nitrogen kjedahl and phosphorus. The temperature measurements were taken daily by a digital thermocouple (top, middle and base of the piles and reactor)... (Completo abstract click electronic access below)

O presente trabalho teve como objetivo estudar o processo de compostagem utilizando dois métodos de tratamento, um convencional e outro mecanizado, para o tratamento dos resíduos de poda/capina e dos resíduos orgânicos gerados nas cantinas da FCT/UNESP. Para a realização deste trabalho, foi quantificada, por meio de pesagens, a geração desses resíduos no campus. O sistema de tratamento convencional por compostagem foi realizado em leiras com revolvimento manual nas proporções mássicas: 70% resíduo de poda/capina (RPC) e 30% resíduo orgânico da cantina (ROC), 50%RPC / 50%ROC e 30%RPC / 70% ROC. O sistema mecanizado foi constituído por um reator de 190 litros na proporção mássica de 50%RPC / 50%ROC, com aeração proveniente do uso de um compressor durante 15 minutos diários. Os parâmetros foram caracterizados ao longo do processo por meio do pH, matéria orgânica, carbono orgânico, resíduo mineral, nitrogênio Kjedahl e fósforo... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Engenharia ambiental; Resíduos; Adubos compostos; Milho - Pesquisa